Clinical and epidemiological profile of COVID-19 patients in the state of Maranhão - Santos da Cruz, José Wagner; Costa de Sousa, Gleciane; de Sousa Vieira Brito, Francilene (Revista Prevenção de Infecção e Saúde, 2023)
Introduction: The COVID-19 is characterized by a severe acute respiratory syndrome with a high fatality rate. Aim: To describe the clinical and epidemiological profile of patients affected by COVID-19 in the state of Maranhão. Outlining: This is an observational, descriptive epidemiological study with quantitative variables collected from the use of the computerized data system of COVID-19 case notifications in the state of Maranhão, during the period between January 1st and August 8th, 2020. Results: Approximately 151,612 confirmed cases of COVID-19 were reported, with a slight predominance of females (55.14%), however the mortality rate was higher among the male population (61.55%). The age group most affected in relation to the contamination rate was adults aged 30 to 39 years (21%), however the death rate from COVID-19 was predominant among elderly people over 70 years of age (55.48%). Regarding the associated comorbidities, there was a greater predominance of cases with arterial hypertension (44.94%) and diabetes mellitus (31.32%). Implications: The rate of infected cases and deaths by COVID-19 in the state of Maranhão is increasing, so the results presented can support the planning of strategies to reduce cases in the target audience identified as most vulnerable.